The Validity of Molecular Geometry Based Virtual Reality to Improve Student Visual-Spatial Intelligence in New Normal Era - Nisa, Ainun; Rifki, Ikfisani Yuniar; Alya, Aiza; Dwiningsih, Kusumawati (Journal of Educational Sciences, 2021)
The Ministry of Education and Culture of the Republic of Indonesia issued policies related to the implementation of education in the new normal era learning systems through online learning by utilizing various technologies. Without face-to-face learning, high school students have difficulty in understanding molecular shape geometry material so that it affects students' ability to develop spatial-visual precepts. As a solution to these problems, there needs to be the development of virtual reality learning videos that match the geometry of molecular shapes in real-time. This study aims to find out the validity of The Virtual Reality-Based Molecular Shape Geometry Tutorial Video As a Solution To Improve the Spatial Visual Ability of High School Students in the New Normal Era. Validity is tested through content quality and purpose, instructional quality, and technical quality. The development was carried out using the R&D method with The Thiagarajan 4D model (Define, Design, Develop, and Disseminate which is limited to the Develop Stage The results were obtained from Virtual Reality Chemistry (VR CHEM) media are very valid on each criterion assessed. The details of the results obtained are content validation of 91.9% and construction validation of 89%.